THE APPLICATION OF ISOTONIC QUADRICEPS EXERCISE IS MORE EFFECTIVE IN INCREASING ELDERLY MOBILITY THAN ISOMETRIC QUADRICEPS EXERCISE PITRA VILLAGE, PENEBEL DISTRICT, TABANAN - Mahardika, Putu Aditya; Tianing, Ni Wayan; Artini, I Gusti Ayu; Wibawa, Ari (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Decreased muscle strength lead to a decline in mobility to the elderly. The purpose of this study to prove that the administration of isotonic quadriceps exercise is more effective in increasing the mobility of the elderly than isometric quadriceps exercise. Experimental research with pre-test and post-test two group design. The mean decrease in group 1 time of 3.79 seconds with p = 0.000 (p <0.05), group 2 occurs an average decrease in time by 2.14 seconds with p = 0.000 (p <0.05). This means that in every group increased mobility significantly. Different test the difference between group 1 and group 2 showed no significant difference with the result p = 0.002 (p <0.05). Based on the results of that study concluded that application of isotonic quadriceps exercise is more effective in increasing the mobility of the elderly than isometric quadriceps exercise. Keywords: Mobility, quadriceps femoris muscle, isotonic quadriceps exercise, isometric quadriceps exercise.